2012
DOI: 10.1111/j.1525-1470.2011.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Acral Milia‐Like Idiopathic Calcinosis Cutis in a Child with Down Syndrome: Report of a Case, Review of the Literature, and Description of Dermoscopic Findings

Abstract: Milia-like idiopathic calcinosis cutis (MICC) is a rare dermopathy, usually occurring in children with Down syndrome. We report a case of an 8-year-old girl with Down syndrome who presented with histologically verified MICC, briefly review the literature on MICC, discuss the differential diagnosis, and describe the use of dermoscopy in the evaluation of lesions, which we believe has never been published previously with this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…3 Clinically, they may resemble warts, epidermal cysts, molluscum contagiosum and syringoma. 4,5 Dermoscopy shows white structures in molluscum contagiosum, epidermal cysts and milia-like calcinosis cutis. 5 We found that central crusts in white homogeneous lesions, corresponding to the transepidermal elimination of calcinosis, are unique features.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Clinically, they may resemble warts, epidermal cysts, molluscum contagiosum and syringoma. 4,5 Dermoscopy shows white structures in molluscum contagiosum, epidermal cysts and milia-like calcinosis cutis. 5 We found that central crusts in white homogeneous lesions, corresponding to the transepidermal elimination of calcinosis, are unique features.…”
mentioning
confidence: 99%
“…4,5 Dermoscopy shows white structures in molluscum contagiosum, epidermal cysts and milia-like calcinosis cutis. 5 We found that central crusts in white homogeneous lesions, corresponding to the transepidermal elimination of calcinosis, are unique features. Since most cases revealed transepidermal elimination, 2 we suggest that the dermoscopic feature of the central crust is useful for the diagnosis.…”
mentioning
confidence: 99%
“…3,4 This disorder is equally frequent in both sexes and most commonly occurs during childhood. 1 Though lesions are frequently found on the hands and feet, they may also appear on other parts of the body. MICC normally disappears spontaneously by adulthood, mostly without scarring, 4 and has mostly been reported as associated with Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…MICC normally disappears spontaneously by adulthood, mostly without scarring, 4 and has mostly been reported as associated with Down syndrome. 1 Although the pathogenesis of MICC is unclear, medical studies have shown that patients with Down syndrome have ectopic calcifications, such as valvular and basal ganglial calcifications. 5,6 MICC has also been reported to occur in patients without Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation